2003
DOI: 10.1063/1.1577809
|View full text |Cite
|
Sign up to set email alerts
|

Infrared optical absorbance of intersubband transitions in GaN/AlGaN multiple quantum well structures

Abstract: Intersubband transitions in Si-doped molecular beam epitaxy grown GaN/AlGaN multiple quantum wells on c-plane sapphire were investigated using the Fourier-transform infrared optical absorption technique. Several GaN quantum well samples were grown with either AlGaN bulk or GaN/AlGaN short period superlattice barriers. The measurements were made in a waveguide configuration utilizing a facet polished at 45° to the c plane. The integrated area of the intersubband transitions in several waveguides cut from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…8,9 We observed that the PL intensity of quantum wells without a capping layer was higher than that of p-GaN capped quantum-well structures because there is intraband absorption in the capped layer. 10 The PL quantum efficiency and full width at half maximum of the QW peak for the LED structure were found to be 0.05% at room temperature and 62 meV at 10 K. The blue emission peak intensity versus inverse temperature gave the activation energy of 43 meV, indicating the localization of the carriers in the structure. The activation energy was increased with increasing In composition, resulting in deep localization energies of excitons due to potential fluctuations.…”
mentioning
confidence: 90%
“…8,9 We observed that the PL intensity of quantum wells without a capping layer was higher than that of p-GaN capped quantum-well structures because there is intraband absorption in the capped layer. 10 The PL quantum efficiency and full width at half maximum of the QW peak for the LED structure were found to be 0.05% at room temperature and 62 meV at 10 K. The blue emission peak intensity versus inverse temperature gave the activation energy of 43 meV, indicating the localization of the carriers in the structure. The activation energy was increased with increasing In composition, resulting in deep localization energies of excitons due to potential fluctuations.…”
mentioning
confidence: 90%
“…These devices are expected to play a particularly important role in applications such as ultra-broadband signal processing and all-optical networking in fiber-optic communication systems, for which near-infrared operation wavelengths near 1.55 μm are required. Material systems with sufficiently large conduction-band offsets to accommodate ISB transitions at these relatively short wavelengths include InGaAs/AlAsSb [1], (CdS/ZnSe)/BeTe [2], and GaN/Al(Ga)N QWs [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Specific advantages of III-nitride semiconductors for ISB alloptical switching include their highly polar nature, which results in a very strong electron-LO phonon coupling and hence particularly fast ISB relaxation lifetimes, and their very wide bandgap, which precludes interband two-photon absorption of near-infrared light. Recently ISB absorption near 1.55 μm has been measured in various GaN/Al(Ga)N QW systems [3][4][5][6][7][8][9], followed by the demonstration of photodetection [10], all-optical switching by crossabsorption saturation [11][12], and optically pumped light emission [13] with similar structures. In addition, several pump-probe measurements in both unprocessed and waveguide samples have fully established the particularly fast nature of ISB relaxation in GaN/Al(Ga)N QWs, with measured lifetimes in the range 140-500 fs [6,7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Initial efforts in the study of ISB transitions in nitride semiconductors have focused on measuring the infrared transmission spectra of various GaN/Al(Ga)N n-doped multiple-QW samples [283][284][285][286][287][288]. Pronounced ISB absorption peaks were reported in these studies, centered at near-infrared wavelengths that could not be accessed using As-based materials.…”
Section: Infrared Device Applicationsmentioning
confidence: 99%